Lyme Disease and Physical Activity: The Impact of the Disease on the Ability to Participate in Sports and the Importance of Prevention in Public Health - Czech, Mateusz; Tarczyński, Dominik; Mazur, Anna; Czmok, Jakub; Radecki, Jakub; Ciesielska, Dominika; Kociuba, Katarzyna; Chojęta, Michał; Brzusek, Mikołaj; Zięba, Natalia; Cisłak, Miłosz (Quality in Sport, 2026)
Background: Lyme disease is an infectious disease caused by various species of Borrelia burgdorferi bacteria transmitted by ticks. Increasing evidence suggests that it may affect an individual's ability to participate in sports and physical activity. Aim of the study: The aim of this study was to summarize the current knowledge regarding the impact of Lyme disease on human body functioning, with particular emphasis on the resulting changes and their consequences for the ability to undertake and engage in physical activity and sports. Material and methods: A narrative literature review was conducted using publications available in the PubMed, Scopus, and Google Scholar databases. Cohort studies, meta analyses, epidemiological studies, experimental studies, and systematic reviews concerning Lyme disease risk factors, preventive strategies, and its impact on physical activity were included. Results: The analysis demonstrated that preventive measures, including post-exposure antibiotic prophylaxis, play a key role in reducing the number of new Lyme disease cases. Such interventions decrease the risk of infection and help limit long-term health consequences. Conclusions: Lyme disease produces neurological, musculoskeletal, and systemic manifestations, including chronic fatigue and pain, which lead to reduced physical performance and diminished exercise tolerance.